Implementation of Leadership Values ​​in Organizations (Case Study of Female Students of Class V TMI Putri Al-Amien Prenduan Academic Year 2023-2024) - Afifah; Fina Alaillah (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Leadership is defined as the ability and readiness to inspire, guide, direct and lead others, meaning that a leader is able to be an inspiration for the community he leads. TMI Putri Al-Amien Prenduan Institution is an Islamic boarding school educational institution that educates its students with an emphasis on community orientation and leadership. This boarding school has succeeded in producing alumni with leadership capacities in various organizational fields. For this reason, it is important to conduct in-depth research on the implementation of leadership values ​​applied in this institution. The type of research conducted is qualitative case study research. Data sources were obtained from Mudir Mahad, Mudir Aam, Head of Santrian Affairs, MPO, Muayrifah, Class V Homeroom Teachers and Class V female students. The data collection methods used were observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. From the results of this study, it was found that the form of implementation of leadership values ​​towards class V female students applied at the TMI Putri Al-Amien Prenduan Islamic Boarding School consists of Theory and Practice. In theory, the activities carried out in the implementation of leadership values ​​are through briefing. The briefing is implemented in the form of KKS (Student Group Leadership), SEKBEN (Secretariat and Treasury) and, LDP/PKM (Basic Training for Supervisors/Leadership and Management Training). While in practice, the implementation of leadership values ​​by the TMI Putri Al-Amien Prenduan institution is attempted in the form of training and assignments. In addition, this study also produced several inhibiting factors in the implementation of leadership values, including internal and external factors. Internal inhibiting factors are caused by the lack of awareness of female students of the importance of leadership values, thus affecting the focus of female students which results in female students not listening and not paying attention during the briefing session. External inhibiting factors are caused by the lack of supervision from homeroom teachers, Mpo Staff, committees and the lack of media or variation in delivering the briefing material.